Estudo da qualidade superficial durante o microfresamento do aço AISI D2 no estado temperado e revenido - Anderson Junior dos Santos (2018)
The production of industrialized products is responsible for most of the job posts in the globalized world. Thus, there is a large demand for miniaturization of components and therefore, the micromilling arises as an alternative to manufacture micro die for the large-scale production of microcomponents which are applied in the aeronautic, automotive, electronics and medical industries. The relevance in the study of the AISI D2 steel micromilling in the quenched and tempered condition is due to the problems found out in the micro die surface quality due to of the slopes (undulations) and burrs formation on the micromachined surfaces, which require an additional surface finishing which is impossible in the most condition due to the high costs and accuracy restriction on the manufactured part. The aim of this work is to evaluate the effect of the feed rate and depth of cutting in the milling operation of channels in AISI D2 steel in the hardened condition, in terms of the machined surface quality, burr formation and wear tools in the dry cutting. The analysis was carried out by monitoring of machining forces signals, acoustic emission and the surface characterization by scanning electronic microscopy (SEM), energy dispersive spectroscopy (EDS) and contact profiling. The results indicate that, for all tests carried out, the wear tool has significant influence in the surface roughness and in the formation of burr due to the material ploughing phenomenon and to the tool deflection which caused mechanical vibrations that are detrimental to the surface quality. The depth of cutting and feed rate were significant for the chip removal by shearing stress, being the feed rate the most significant parameter for the material ploughing effect.